Külső és belső határok a Nyugat-Balkán regionális térfelosztásában - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2011)
The aim of this paper is to examine the historical development of Yugoslavia’s internal and international borders from the time of its creation in 1918 to the secessions of four of its republics in 1991. The creation of Yugoslavia in the wake of World War I led to a number of territorial disputes with neighbouring states, all of which were resolved by the mid-1920s. During its history, the structure of Yugoslavia’s internal administrative units was a matter of considerable controversy and change on the most appropriate means of successfully keeping together a multinational state. The interwar Kingdom of Yugoslavia saw the consecutive adoption of three different structures, and the fourth internal administrative arrangement established immediately after World War II by the new communist government. The paper discusses the impact of the international border after breaking up of Yugoslavia during the early 1990s. All successor four republics being recognized as independent states within the international community of states. In each case the international borders of the new states corresponded with internal federal borders as they existed at the time of independence. The major legal principle relied upon by the Commission was that of uti possidetis juris. Finally the paper shows the most hotly contested land-border disputes between the Yugoslav successor states.